Teaching to Different Personality Types - Alexa J. Lamm; Ricky W. Telg (EDIS)
A person’s personality affects the way he or she learns best. Extension programs can use an understanding of different learning styles and preferences to reach the greatest number of people. This EDIS document is the first in the Teaching to Different Personality Types series, and provides a broad overview of how understanding and acknowledging personality types can assist in Extension program development. Written by Alexa J. Lamm and Ricky W. Telg, and published by the UF Department of Agricultural Education and Communication, September 2015. (Photo credit: Rawpixel Ltd/iStock/Thinkstock.com)